2011
DOI: 10.4306/pi.2011.8.3.262
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in the HTR2C and Peroxisome Proliferator-Activated Receptors Are Not Associated with Metabolic Syndrome in Patients with Schizophrenia Taking Clozapine

Abstract: ObjectiveGenetic variation in the serotonin-2C receptor encoded by the HTR2C gene is one of the genetic determinants of antipsychotic-induced weight gain. Peroxisome proliferator-activated receptors are nuclear receptors regulating the expression of genes involved in lipid and glucose metabolism. In this cross-sectional study, we investigated whether HTR2C-759C/T, HTR2C-697G/C, PPARα V227A, and PPARγ 161C/T genotypes were associated with metabolic syndrome (MetS) in patients with schizophrenia taking clozapine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…From the 20 studies assessed in detail, 1 was excluded because no information about the HTR2C -759 C/T genotype or allelic frequencies was given (Gunes et al 2009), 2 were excluded because no detailed number of the patients having high weight gain and low weight was given (Ujike et al 2008a;Laika et al 2010), 7 were excluded because multiple types of SGAs were used to assess the SGA-induced weight gain without being broken down into separate groups with detailed numbers of the patients with high or low weight gain (Reynolds et al 2002;Templeman et al 2005;Mulder et al 2007b;Ryu et al 2007;Opgen-Rhein et al 2010;Sicard et al 2010;Gregoor et al 2011). A total of 10 studies were included in the current meta-analyses and their data were extracted; among them, 4 were included in the meta-analysis of the HTR2C -759C/T polymorphism and olanzapine-induced weight gain Kuzman et al 2008;Park et al 2008;Godlewska et al 2009), 6 were included in the meta-analysis of the HTR2C -759C/T polymorphism and olanzapine/clozapine/risperidone-induced metabolic syndrome (Yevtushenko et al 2008;Kuzman et al 2011;Mulder et al 2007aMulder et al , 2009Kang et al 2011;Risselada et al 2012); among the later 6, 3 were further included in the meta-analysis of the HTR2C -697G/C polymorphism and olanzapine/clozapine/risperidone-induced metabolic Total potentially eligible studies, N=27 Studies excluded through screening:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the 20 studies assessed in detail, 1 was excluded because no information about the HTR2C -759 C/T genotype or allelic frequencies was given (Gunes et al 2009), 2 were excluded because no detailed number of the patients having high weight gain and low weight was given (Ujike et al 2008a;Laika et al 2010), 7 were excluded because multiple types of SGAs were used to assess the SGA-induced weight gain without being broken down into separate groups with detailed numbers of the patients with high or low weight gain (Reynolds et al 2002;Templeman et al 2005;Mulder et al 2007b;Ryu et al 2007;Opgen-Rhein et al 2010;Sicard et al 2010;Gregoor et al 2011). A total of 10 studies were included in the current meta-analyses and their data were extracted; among them, 4 were included in the meta-analysis of the HTR2C -759C/T polymorphism and olanzapine-induced weight gain Kuzman et al 2008;Park et al 2008;Godlewska et al 2009), 6 were included in the meta-analysis of the HTR2C -759C/T polymorphism and olanzapine/clozapine/risperidone-induced metabolic syndrome (Yevtushenko et al 2008;Kuzman et al 2011;Mulder et al 2007aMulder et al , 2009Kang et al 2011;Risselada et al 2012); among the later 6, 3 were further included in the meta-analysis of the HTR2C -697G/C polymorphism and olanzapine/clozapine/risperidone-induced metabolic Total potentially eligible studies, N=27 Studies excluded through screening:…”
Section: Resultsmentioning
confidence: 99%
“…Studies included in the meta-analysis of -759C/T and olanzapine/clozapine/risperidoneinduced metabolic syndrome, N=6 (Of the 6, studies further included in the metaanalysis of -697G/C and olanzapine/clozapine/risperidone-induced metabolic syndrome, N=3; studies further included in the meta-analysis of intragenic rs1414334:C>G polymorphism and olanzapine/clozapine/risperidone-induced metabolic syndrome, N=3) syndrome (Mulder et al 2007a(Mulder et al , 2009Kang et al 2011), and 3 were further included in the meta-analysis of the HTR2C rs1414334:C Ͼ G polymorphism and olanzapine/clozapine/ risperidone-induced metabolic syndrome (Mulder et al 2007a(Mulder et al , 2009Risselada et al 2012). Th e characteristics of the 10 studies included in the current meta-analysis were described in Tables IA and IIA including year of publication, study design, number of total sample, gender ratio, subjects ' prior antipsychotic medication, diagnostic tools for defi nition of high weight gain and low weight gain for the meta-analysis of the HTR2C polymorphism and olanzapine-induced weight gain, and for defi nition of metabolic syndrome for the meta-analysis of the HTR2C polymorphisms and olanzapine/clozapine/risperidone-induced metabolic syndrome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though a few researchers have studied the change in prevalence rates over time, largely the estimates have been cross-sectional. Amongst the cross sectional studies, as depicted in Table 1,[101112131415161718192021222324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899] most studies have evaluated the patients who are already on treatment and only a few have assessed the prevalence of MetS in drug naive population. Most of the studies have ...…”
Section: Prevalence Of Metabolic Syndrome In Schizophreniamentioning
confidence: 99%
“…Herken et al detected that there was PPARγ gene polymorphism in schizophrenia patients who were administered olanzapine and who had weight gain in their study [8]. In another clinical study, both PPARγ and PPARγ gene was presented to be related with the weight gain induced by clozapine, similar to olanzapine, and the MetS [9]. In a study examining the effects of PPARγ agonists on the cognitive functions in schizophrenia patients treated with clozapine, it was shown that PPARγ agonists do not have any positive effects on the cognitive functions [10].…”
Section: Discussionmentioning
confidence: 96%